Microfinance and women's empowerment: an ethnographic inquiry*. Issue 1 (2nd January 2016) - Geleta, Esayas Bekele
ABSTRACT: Within the last two decades microfinance has been widely adopted as one of the best development strategies to reduce poverty and empower women in many developing countries. Drawing on ethnographic research undertaken in Ethiopia, this article elucidates the complexities of microfinance processes, and argues that current microfinance practice does not facilitate the participation of women in decision-making over the use and management of loans as well as the income they generate from running small enterprises. The article illustrates that women are engaged in running small-scale economic activities at home that produce low returns, and they have limited access to lucrative markets. It also demonstrates that due to a discriminatory household division of labour, women are overworked in their households and in their enterprises. Through engaging in a mode of representation (ethnography) that allows specific critical voices to be heard, the article contributes toward tempering the current enthusiasm for the widely expanding microfinance industry.